Defense and detection strategies against Internet worms - Nazario, Jose (Artech House computer security series., 2004)
This is the first book focused exclusively on Internet worms, offering you solid worm detection and mitigation strategies for your work in the field. This ground-breaking volume enables you to put rising worm trends into perspective with practical information in detection and defense techniques utilizing data from live networks, real IP addresses, and commercial tools. The book helps you understand the classifications and groupings of worms, and offers a deeper understanding of how they threaten network and system security.